شروط ترجمة المصطلحات القرآنية وضوابطها - بن عبد النور, احمد; قلو , ياسمين (Maalim, 2019)
ملخّص: الترجمة، وبالرغم من كونها وسيلة تخاطب وتفاهم، إلاّ أنّها لا تحقق التكافؤ في النقل بالنّظر إلى التباعد اللغوي والثقافي، والترجمة اجتهاد تحكمه الخلفيات الخاصة بالمترجم وآراؤه الشخصية لحدّ ما. ويزيد الإشكال مع القرآن، ذلك النصّ المقدّس، وحاز موضوع ترجمة معاني القرآن على إهتمام الباحثين والنقاد والمترجمين. أثرنا في هذا البحث أن ندرس موضوع ماهيّة المصطلحات الدينية وترجمتها، من الجزئية المتعلّقة بقابلية ترجمة القرآن ومنه لننتقل إلى ضبط المصطلح كمفهوم، فالحدود الواجب مراعاتها في ترجمته محاولةً منّا لإستنتاج شروط الترجمة. Abstract: Translation, although being a means of understanding, it doesn’t guarantee the exact equivalence. The most important reason is the linguistic differences between languages and different cultures. The perception of the original text in translation is different depending mainly upon the translator’s emotions, background and beliefs, especially when faced with a sacred text ( the Qur'an for example). Therefore, the translating issues related to the meanings of the Qur'an have attracted the researchers’ attention. In this piece of research, we shed light on the translation of religious texts based on terminology with religious and cultural dimensions to finally conclude some of the conditions that sgould be available in the translator.